Wellbeing in telework: a systematic review of leadership competencies - Bravo-Duarte, Felipe; Tordera, Núria; Rodríguez, Isabel (Frontiers in Organizational Psychology, 2025)
IntroductionIn the context of Industry 5.0, organizations are experiencing significant changes in work arrangements, particularly through telework settings. Leaders face new challenges in reducing virtual distance, which also affects employee wellbeing in remote contexts. This systematic literature review examines empirical evidence on leadership competencies that promote teleworkers' wellbeing and analyzes the mechanisms and conditions under which these relationships occur.MethodsWe analyzed 31 empirical articles (23 quantitative and eight qualitative) published between 2000 and 2024 following PRISMA guidelines. The review focused on research examining leadership competencies in telework contexts and their relationship with different dimensions of wellbeing (hedonic, eudaimonic, and health-related).ResultsThe review identified five key leadership competencies positively related to teleworkers' wellbeing. These include competencies for reducing operational distance (digital communication and goal management) and affinity distance (supervisor support, work-life facilitation, and participative leadership). Work-to-family enrichment, autonomy, and trust emerged as mediating mechanisms. Leaders' emotional intelligence, digital skills, and employees' work-life segmentation preferences were identified as relevant boundary conditions.DiscussionWhile traditional leadership competencies remain important, they require substantial adaptation to reduce virtual distance and promote wellbeing in telework environments. The findings reveal gaps in current research, particularly regarding longitudinal studies and team-level outcomes. The results provide guidelines for developing leadership training programs that emphasize leaders' support, effective digital communication, and balanced goal management in telework contexts while considering specific mechanisms and contextual variables.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023473498, identifier: CRD42023473498.